HUBUNGAN KETERATURAN KUNJUNGAN ANTENATAL CARE TERHADAP KEPATUHAN KONSUMSI TABLET FE PADA IBU HAMIL DI JAWA TENGAH (ANALISIS SDKI 2017) - Wibowo, Syifa Sofia (Dian Nuswantoro Semarang, 2025)
Background: According to the 2018 Riskesdas data, anemia affects 48.9% of pregnant women in Indonesia. Every pregnant woman is expected to take at least 90 Fe tablets during her pregnancy to prevent anemia. Anemia caused by iron deficiency increases the likelihood of difficulties during delivery. Anemia creates risks not only to the mother but also to the fetus and newborn. Methods: Data from the 2017 Indonesian Demographic Health Survey (IDHS) Program was used in this study. This study used a cross-sectional design. With a sample of 118 respondents. Results: The average mother already had 3 children; the average pregnant woman was 35 years old at the current pregnancy and the average mother's education was not graduated from primary school. The significance value between regularity of antenatal care visits and adherence to Fe tablet consumption in pregnant women is 0,000. Conclusion: There is an association between regularity of antenatal care visits and adherence to Fe tablet consumption by pregnant women in Central Java in the 2017 IDHS data.